Switching to insulin degludec/aspart penfill reusable cartridges in patients with type 2 diabetes mellitus: real-life outcomes - Sezin Dogan Çakır; Hatice Deniz Yücel; Zeynep Akgül Kızılçay; Mine Adaş (Diabetology & Metabolic Syndrome)
Abstract Aims This study aimed to evaluate the clinical outcomes of switching from disposable insulin delivery pens to reusable insulin pens with a penfill cartridge system for the co-formulation of insulin degludec and insulin aspart (IDegAsp) in patients with type 2 diabetes (T2D) in Türkiye. We assessed the impact on glycemic control to evaluate the sustainability of this transition. Methods A total of 226 adults with T2D who were initiating or switching to IDegAsp reusable cartridge insulin pens at a tertiary center in Türkiye were followed for 6 months. Data were retrospectively extracted from the medical records at baseline (prior to switching) and at follow-up visits after 3 and 6 months of IDegAsp Penfill reusable cartridges. Results Initiating the IDegAsp reusable cartridge insulin pen in patients who previously used basal-bolus, basal, or premixed insulin therapies with disposable insulin pens was associated with a significant reduction in mean glycated hemoglobin (HbA1c) [mean change -1.0% (95% confidence interval (CI) − 2.2 to − 0.20; p < 0.001)], [− 1.4% (95% CI − 2.3 to − 0.4; p < 0.001)], and [− 0.9% (CI − 1.7 to − 0.1; p < 0.001)]. Switching from IDegAsp disposable insulin pens to the reusable system demonstrated noninferior outcomes [− 0.08% (CI − 0.2 to 0.1; p = 0.629)]. The mean total daily insulin dose and body weight were also significantly lower in patients who were switched from basal-bolus insulin, basal insulin or premixed insulin therapies (p < 0.001 and p < 0.001, respectively). Conclusion Initiating or switching to the IDegAsp reusable pen with the insulin cartridge system in a real-world population of people with T2D in Türkiye was associated with improved or maintained glycemic control.